2020
DOI: 10.1111/cpr.12964
|View full text |Cite
|
Sign up to set email alerts
|

20‐HETE synthesis inhibition attenuates traumatic brain injury–induced mitochondrial dysfunction and neuronal apoptosis via the SIRT1/PGC‐1α pathway: A translational study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…EX527 was dissolved in 1% DMSO (in physiologic saline) and then added to culture medium to reach a final concentration of 20 mM. The doses of SRT1720 and EX527 were selected according to previous studies (31)(32)(33).…”
Section: Drug Administrationmentioning
confidence: 99%
“…EX527 was dissolved in 1% DMSO (in physiologic saline) and then added to culture medium to reach a final concentration of 20 mM. The doses of SRT1720 and EX527 were selected according to previous studies (31)(32)(33).…”
Section: Drug Administrationmentioning
confidence: 99%
“…In the ischemia-reperfusion injury, inhibition of 20-HETE synthesis reduced oxidative stress and the expression of vascular TNFα, IL-1β and IL-6 ( Regner et al, 2009 ; Hoff et al, 2011 ). In addition, Han et al found that the use of 20-HETE synthesis inhibitor HET0016 to inhibit the synthesis of 20-HETE can reduce the volume of brain injury and neurological deficit, alleviating neuronal death, ROS production, gelation activity, and inflammatory reaction, which indicates that inhibition of 20-HETE synthesis protects brain injury after intracerebral hemorrhage without inhibiting angiogenesis ( Han et al, 2019 ; Cui et al, 2021 ). Inhibition of 20-HETE production can also attenuate kidney injury in a rodent model of acute kidney injury (AKI) induced by ischemia/reperfusion (I/R) ( Hoff et al, 2011 ; Hoff et al, 2019 ).…”
Section: The Roles Of Cytochrome P450 ω-Hydroxylase-mediated Eicosanoids In Inflammation-associated Diseasesmentioning
confidence: 99%
“…As mentioned previously, primary cortical neurons (PCNs) from E17 C57BL/6 mouse embryos were isolated and cultured [24]. Brie y, the embryonic mouse brains were removed with sterilized instruments after the pregnant mice were executed.…”
Section: Neuron Culturementioning
confidence: 99%